Sociology of Religion 2019
DOI: 10.4324/9781315177458-25
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Encounters and Manhood Acts: Evangelicals, Latter-Day Saints, and Religious Masculinities

Abstract: The experiences of men in traditional religions are complex, at times inconsistent, and not necessarily the direct result of religious teachings. This article draws from two qualitative case studies to examine the ways in which evangelical and Latter-Day Saint men understand masculinity and their spiritual beliefs in the context of sexual activity. The authors present two masculine practices-acceptance of sexual rejection and sexual indifference-that allow religious men in this study to simultaneously challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Religion is an important predictor of sexual attitudes and beliefs (e.g., Burke and Hudec 2015; Diefendorf 2015; Sumerau 2012). To account for religion, we use the question “What is your religion, if any?” utilizing the following categories for religious affiliation.…”
Section: Methodsmentioning
confidence: 99%
“…Religion is an important predictor of sexual attitudes and beliefs (e.g., Burke and Hudec 2015; Diefendorf 2015; Sumerau 2012). To account for religion, we use the question “What is your religion, if any?” utilizing the following categories for religious affiliation.…”
Section: Methodsmentioning
confidence: 99%
“…Although an under-researched topic, the relationship between religion, men, and masculinities is gaining scholarly attention, especially in the USA where research has mainly focused on Christian evangelicals (e.g., Burke & Hudec, 2015;Gallagher & Smith, 1999;Gerber, 2015;McDowell, 2017). Studies of the evangelical Promise Keepers movement have found that its male leaders and adherents support varying gender ideologies, ranging from conservative-traditional to progressive-egalitarian (Heath, 2003;Lockhart, 2000).…”
Section: Researching Christian Men and Masculinitiesmentioning
confidence: 99%
“…Importantly, the norms and guidance that youth receive regarding sex vary by these group memberships (Burdette, Hill, and Myers ; Regnerus ). For example, evangelical Protestant subculture is known for having especially proscriptive attitudes toward premarital sexual activity, and there are a large number of books, materials, and resources specifically geared toward encouraging sexual abstinence before (heterosexual) marriage (Burke and Hudec ; Gardner ; Irby ). Many youth and young adults from conservative traditions also participate in gender‐specific small groups in order to share their struggles, encourage one another, and serve as accountability partners for temptations and violations of sexual prohibitions (Diefendorf ; Irby ).…”
Section: Theory and Backgroundmentioning
confidence: 99%